(3GdbGfhf GdOSJhQj h GdfXe GdSjGSjI GdebGQfI (B:s (3GdLRA GdKGfj (B/s - (3HhGdTYjQ, SYjOs ((3GdLRGFQ (B:s (3OjhGf GdeWHhYGJ GdLGeYjI ,s, 1988)
(3jJfGhd GdcGJH aj gPG GdLRA HGdOQGSI h GdJMHdjd GdGSS GdGbJUGOjI h GdGLJeGYjI h GdSjGSjI dGfXeI GdSjGSjI GdebGQfI (B. (3GeG GdbSe GdKGfj ajJfGhd HJMdjd GdLGfH GdbGfhfj h GdJWHjbj dJdc GdGfXeIs
(3HjHdjhZQGajG(B:(3U(B.345-348s
Keywords: (3GdLRGFQs; (3GdSjGSIs; (3GdbGfhf GdOSJhQjs; (3Ydhe SjGSjI s